(untitled) (Journal of Hama University, 2024)
Endodontic surgery has become a standard of care for dental maintenance if conventional endodontic retreatment is not able to eliminate the infection, The aim of this research is to evaluate the Edema formation after Microsurgical Endodontics using piezo surgical tips and rotation burs. The sample size comprised 32 teeth according to inclusion criteria from the patient that came to dentistry collage of Hama university. The results showed that there was a significant difference (P<0.05), after three days mentoring period between piezo surgery and rotation burs groups, and according to statistical results the edema formation is higher in piezo surgery group than rotation burs group after three days mentoring period. After collecting the responses data were analyzed using Mann-Whitney U at the 0.05 level of significance.